Physical activity and gross motor skills in rural South African preschool children - Tomaz, Simone Annabella (Division of Exercise Science and Sports Medicine, 2019)
Background: Global levels of overweight and obesity in preschool-aged children have increased dramatically in the last two decades, with most overweight and obese children younger than five years living in low- and middle-income countries (LMICs). Statistics from the 2013 South African National Health and Nutrition Examination Survey (SANHANES-1) confirm that levels of overweight and obesity are high in South African preschool-aged children, with prevalence rates of overweight and obesity up to 18.2% and 4.7%, respectively. This increasing problem of overweight and obesity in South African preschoolaged children highlights the need for intervening in this age group. Overweight and obesity interventions in preschool children typically include one or more of the following behaviours: physical activity, sedentary behaviour and screen time. Aim and objectives: The aim of this study was to characterise the preschool environment in rural South Africa, and to explore physical activity, gross motor skill proficiency, sedentary behaviour and screen time in rural South African preschool-aged children. Additionally, aims of this study were to explore the associations between gross motor skills, body composition and physical activity; and to assess compliance with current physical activity and sedentary behaviour guidelines. Methods: Preschool-aged children (3-5 years old, n=131) were recruited from three Preschools and two Grade R (reception year) settings in Agincourt, a rural village in north eastern South Africa. In order to gain an understanding of the Preschool and Grade R settings, an observation of the preschool environments was conducted using a tool adapted from the Outdoor Play Environmental Categories scoring tool, Environmental and Policy Assessment and Observation instrument, and the Early Learning Environments for Physical Activity and Nutrition Environments Telephone Survey. Each child’s height and weight was measured. Physical activity and sedentary behaviour were measured objectively using a hip-worn ActiGraph GT3X+ accelerometer for 7 days (24 hours, only removed for water-based activities). Gross motor skills were assessed using the Test for Gross Motor Development–Version 2 (TGMD-2). Physical activity and sedentary behaviour, including the contextual information for these behaviours, during the preschool day (08h00 until ±12h00) were measured using the Observational System for Recording Physical Activity in Children (Preschool Version). A separate sample of parents/caregivers were recruited (n=143) to complete a questionnaire that was adapted from the Healthy Active Preschool Years questionnaire and Preschool Physical Activity Questionnaire. Parents reported on their child’s screen time, and on factors within the home and community contexts in which physical activity and sedentary behaviours occur. Results: In terms of the environment, the Preschools and Grade R settings differed in that fixed play equipment only featured in the Preschool settings. Grade R settings had more open space in which to play. All Preschool and Grade R settings provided children with limited portable play equipment, and none of the schools had access to screens. Although all children recruited for the study were preschool-aged, the Grade R children were significantly older than the Preschool children (5.6±0.3years vs. 4.4±0.4 years, p <0.05). According to IOTF cut-offs, the prevalence of overweight/obesity was low (5.0%) in the sample, and 68.1% of children were classified as normal weight. On average, children spent 477.2±77.3 minutes in light- to vigorous-intensity physical activity (LMVPA) per day, and 93.7±52.3 minutes in moderate- to vigorous-intensity physical activity (MVPA). In terms of the new current guidelines (180min/day LMVPA, including 60min of MVPA, described as ‘energetic play’), and using average daily average of LMVPA and MVPA, 78.2% met current guidelines. Observed and objectively measured sedentary behaviour results revealed that children were more sedentary during preschool time (between 08:00 to 12:00) compared to the afternoons. Overall, boys were significantly more physically active than girls; and Preschool children did more physical activity during preschool time than Grade R children (all p< 0.05). Over 90% of the sample achieved an ‘average’ or better ranking for gross motor skill proficiency. The Grade R children were significantly more proficient than the Preschool children for all gross motor skill components (raw scores and standardised scores). Overall, boys achieved significantly better object control raw scores than the girls, and displayed greater proficiency than the girls in the strike (p=0.003), stationary dribble (p< 0.001) and kick (p< 0.001). None of the preschool or Grade R settings had access to screens such as televisions or iPads, and parent-reported screen time was low for the total sample (0.5±0.3hr/day). The majority of the sample (97.9%) met current screen time guidelines (<1 hour per day). Parents (82.5%) reported that they believed that their child did sufficient PA for their health, but 81.8% also reported believing that television time would not affect their child’s health. Parent responses revealed neighbourhood safety as a potential barrier to being physically active in the community. Conclusions: Rural preschool-aged children in South Africa appear to be engaged in adequate amounts of physical activity, particularly LMVPA, and are adequately proficient in gross motor skills. The children did not engage in excessive amounts of screen time. Overweight and obesity were not prevalent in this sample of rural preschool-aged children, and therefore it would appear that an intervention to reduce or prevent obesity by increasing physical activity, improving gross motor skills and reducing screen time is unnecessary. Rather, interventions that facilitate the increase in levels of MVPA in order to meet current physical activity guidelines are warranted. Additionally, it is essential that the high levels of physical activity (LMVPA) and good foundation of gross motor skills observed in this sample are promoted in an effort to maintain them throughout childhood. Future research may want to determine whether these activities (high levels of LMVPA, low levels of screen time) track throughout childhood and into adolescence.